Respon Pertumbuhan Bibit Mangrove Rhizophora Apiculata B1 pada Media Tanah Topsoil - Rizki, Rizki; Novi, Novi (Universitas PGRI Sumatera Barat, 2017)
This study aims to determine the growth of mangrove seedlings grown on soil top soil media. Mangrove seeds obtained from the community around the mangrove forest in Taluak Buo Bungus, Padang. This study used experimental method using Completely Randomized Design (RAL) consisting of 4 treatments and 6 replications. Treatment A as a control using land taken from the mangrove forest area of Taluak Buo Bungus, Padang. Treatment B using 100% topsoil soil, Soil top soil treatment (70%) plus cow manure. Treatment of soil top soil (70%) with the addition of chicken manure. Growth factor to be observed in this research is the growth of stem and number of leaves, then also calculated stem diameter ratio at all treatment. The results showed that the treatment on seed height and number of leaves was significantly different with the control, while for the number of different leaves were not real.